Links between carbon, deforestation and conflict in Colombia - Ganzenmüller, Raphael; Castro-Nuñez, Augusto (2019)
The project “Implementing sustainable agricultural and livestock systems for simultaneous targeting of forest conservation for climate change mitigation (REDD+) and peace-building in Colombia” aims to contribute towards the reduction of landbased GHG emissions, conserving forest, restoration of degraded landscapes and improving rural livelihoods, while stimulating peace-building in rural Colombia. This report adds to Activity l.2 of the project by providing a data driven analysis of geographical overlaps between priority areas for peace-building and land-based climate change mitigation.